(untitled) (Bulletin KNOB, 2013)
In 1655-1656 the ceilings of the Weeskamer and the Thesaurie Ordinaris of the Amsterdam town hall were painted by Cornelis Holsteijn, that of the Justitiekamer by Nicolaes van Helt Stockade and that of the Burgemeesterskamer by Jan van Bronkhorst. The allegorical representations of justice, against the backdrop of a blue sky, are embedded in the architectural structure of the rooms on the first floor. In 2006, the Stichting Restauratie Atelier Limburg was commissioned to study the effects that natural aging and interventions done in the past had had on the linen canvas and the painter’s materials that had been used. The fact that smalt, a blue pigment that turns grey over time, was used for the sky parts had repeatedly led to extensive restorations. The 19th-century wax-resin canvasses no longer provided sufficient support and extensive repainting of the original surfaces – which in turn also suffered from discoloration – made it necessary to intervene again. The restoration consisted of urgent conservative interventions to make the canvas robust again and an extensive cleaning of the painted surface to bring to light the trompe-l’oeil effect again. By removing the much yellowed and shiny layers of varnish as well as the discoloured repainted parts, the original rendition of space in the painted ceilings was done justice again. The reconstruction of the authentic colours of the architecture was done on the basis of information gained from elements that had never been painted over. The combined interventions restored the ensemble to its former unity.